Toward coexistence and sharing between IMT-Âadvanced and existing fixed systems - Shamsan, Zaid A.; Syed Yusof, Sharifah Kamilah; Abd. Rahman, Tharek (Computer Science and Security (CSC), 2008)

(untitled)
In this paper coexistence and spectrum sharing between systems as a recently critical issue due to emerging new wireless technologies and spectrum scarcity are investigated. At World Radiocommunication Conferences 2007 (WRC-07), International Telecommunication Union - Radiocommunications (ITU-R) allocated 3400-3600 MHz band for the coming fourth generation (4G) or IMT-Advanced on a co-primary basis along with existing Fixed Wireless Access (FWA) systems. Therefore, coexistence and sharing requirements like separation distance and frequency separation coordination must be achieved in terms of both co-channel and adjacent channel frequencies. Co-sited the two base stations antennas and non co-sited coexistence of the two systems are analyzed. The interference analysis models, Adjacent Channel Interference Ratio (ACIR) and spectrum emission mask are applied in the 3.5 GHz band to extract the additional isolation needed to protect adjacent channel interference. Also interference to noise ratio as a standard interference criteria is introduced. Finally, possible intersystem interference mitigation techniques are suggested and explained.